Sex differences in estimated brain metabolism in relation to body growth through adolescence. Issue 3 (March 2019) - Vandekar, Simon N; Shou, Haochang; Satterthwaite, Theodore D; Shinohara, Russell T; Merikangas, Alison K; Roalf, David R; Ruparel, Kosha; Rosen, Adon; Gennatas, Efstathios D; Elliott, Mark A; Davatzikos, Christos; Gur, Ruben C; et al.
The human brain consumes a disproportionate amount of the body's overall metabolic resources, and evidence suggests that brain and body may compete for substrate during development. Using perfusion MRI from a large cross-sectional cohort, we examined developmental changes of MRI-derived estimates of brain metabolism, in relation to weight change. Nonlinear models demonstrated that, in childhood, changes in body weight were inversely related to developmental age-related changes in brain metabolism. This inverse relationship persisted through early adolescence, after which body and brain metabolism began to decline. Females achieved maximum body growth approximately two years earlier than males, with a correspondingly earlier stabilization of brain metabolism to adult levels. These findings confirm prior findings with positron emission tomography performed in a much smaller cohort, demonstrate that relative brain metabolism can be inferred from noninvasive MRI data, and extend observations on the associations between body growth and brain metabolism to sex differences through adolescence.